2016
DOI: 10.1038/srep35214
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pre-operative Renal Insufficiency in Urothelial Carcinoma: A Systematic Review and Meta-Analysis

Abstract: The effect of pre-operative renal insufficiency on urothelial carcinoma (UC) prognosis has been investigated by numerous studies. While the majority report worse UC outcomes in patients with renal insufficiency, the results between the studies differed wildly. To enable us to better estimate the prognostic value of renal insufficiency on UC, we performed a systematic review and meta-analysis based on the published literature. A total of 16 studies which involved 5,232 patients with UC, investigated the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 47 publications
1
32
1
Order By: Relevance
“…The NLR, calculated as the absolute neutrophil count divided by the absolute lymphocyte count, has often been investigated as a potential indicator in various tumors [49-51]. Bladder cancer is still a challenging issue, especially the muscle-invasive and metastatic diseases, and efforts to explore and validate prognostic biomarkers for use in the personalized treatment of bladder cancer, mUC or uUC carcinoma patients are urgently required [5, 6, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…The NLR, calculated as the absolute neutrophil count divided by the absolute lymphocyte count, has often been investigated as a potential indicator in various tumors [49-51]. Bladder cancer is still a challenging issue, especially the muscle-invasive and metastatic diseases, and efforts to explore and validate prognostic biomarkers for use in the personalized treatment of bladder cancer, mUC or uUC carcinoma patients are urgently required [5, 6, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Established predictors of prognosis include older age (>70-75 yr), tumour stage, tumour location, lymphovascular invasion (LVI), lymph node involvement [8], and mode of recurrence [9,10]. Recent evidence has suggested that preoperative renal insufficiency indicates poor prognosis in patients with MIBC and UTUC [11][12][13][14][15]. However, the impact of preoperative renal impairment severity on prognosis in urothelial carcinoma remains unelucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested kidney and urinary tract cancers are high risk for renal dysfunction due to the tumor location (obstruction, and/or reduction of nephron mass) [13,[15][16][17]. The prevalence of CKD in genitourinary cancers were reported 8.7-21.4% [15,18]. In the present study, the prevalence of CKD in MIBC patients was 37%, which is a strong bias in our cohort.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, there was no significant difference between the number of CKD patients with CVD (n=35/68, 52%) and without CVD (n = 218/513, 42%) ( Figure 5E). Therefore, as previous study suggested [18], bladder cancer is great potential to have a renal dysfunction during the disease progression. Although there is no clear explanation for that, the effects of metabolic syndrome [19] and chronic inflammation may explain the association of CKD and oncological outcome [20,21].…”
Section: Risk-score-based Protocol Months After Rcmentioning
confidence: 99%